Working Their Way into the Scientific Culture: Women Challenging and Transforming the Discourse. - Davis, Fran; Steiger, Arlene (Textual Studies in Canada)
The article juxtaposes the voices of students, particularly women students, to a scientific text that illustrates those aspects of the culture which have been particularly exclusionary of women. The scientific text chosen is a historic paper "Molecular Structure of Nucleic Acids: A Structure for Deoxyribose Nucleic Acid." For many feminists, the dissatisfactions of women students have represented the hope for a transformation of science education and ultimately of science itself. However, it must be said that much about science education dulls their critical edge. The very pace which imposes so much discomfort upon students militates against the kind of individual and collective reflection which might bring about a transformation of their condition. In short, science students are so busy working that they do not have time to think. The situation is compounded, moreover, by the fact that the hierarchical ordering of the material also tends to defuse criticism. Despite the obvious feelings of ambivalence that one hears from women all the time, it would be a mistake to underestimate the attraction of high-status careers for young women entering science programs.